Professionals' health conceptions of clients with psychosocial problems: An analysis based on an empirical exploration of semi-structured interviews - Fia van Heteren; Nadine Raaphorst; Sandra Groeneveld; Jet Bussemaker (Elsevier, 2023)
Background: The care of clients with complex psychosocial problems involves diverse frontline professionals such as general practitioners, psychiatric nurses, police officers, social support consultants and debt counselors. As these professionals have different professional backgrounds and work in different organizations, their health conceptions, or beliefs about what constitutes health and how this should be pursued, may also differ. Having an understanding of various frontline professionals' health conceptions is relevant, as these may affect interprofessional collaboration in their work with clients with psychosocial problems. Objective: To understand various frontline professionals' health conceptions. Design: Inductive qualitative approach. Setting: The Hague, the Netherlands. Participants: Various frontline professionals from social welfare, general healthcare and mental healthcare, working with clients with complex psychosocial problems. Methods: Between September 2020 and April 2021, 23 in-depth semi- structured interviews were conducted with frontline professionals in social welfare, general healthcare and mental healthcare. Based on these interviews, this paper analyzes frontline professionals' health conceptions. After transcription, all interviews were imported into ATLAS.ti for analysis. An iterative process of thematic analysis was used to identify health conception dimensions. Results: The paper found that frontline professionals' health conceptions differ in three main aspects: 1) health definitions, 2) alignment with clients and 3) contextualization of clients' health. Conclusions: The main implication of this research is that this inductive analysis of health conceptions provides a first building block in theorizing frontline professionals' health promotion practices. Tweetable abstract: Knowing about professional's health conceptions gives insight into how health is understood and how good health can best be achieved, which is important in caring for vulnerable clients.